The Role Of Government In Pandemic, To Overcome The Survey Of Unemployment And Poverty In The National Economic Recovery In The Supporting A Defense Economy - Eva Haryatie (Kusuma Negara Business School, 2022)
In early 2020, the world was shocked by a new pneumonia outbreak that started in Wuhan, Hubei Province and then spread quickly to 190 countries and territories. This outbreak was named corona virus disease 2019 (COVID-19). The corona virus disease 2019 (covid-19) pandemic has had an impact on social, economic, tourism and all community welfare aspects and its handling cannot be separated from efforts to recover the national economy because the impact of the covid-19 pandemic has caused a drastic decline in various economic activities that endanger the national economy. Government policy in Presidential Regulation (Perpres) Number 82 of 2020, namely regarding the committee for handling Covid-19 and national economic recovery, has formed a committee for handling Covid-19 and national economic recovery, the joining of ministries from various aspects has joined together to assist in coordinating the implementation of government strategic policies in the framework of the recovery of the national defense economy. This research aims to identify and explain the government's role in recovering the national economy during a pandemic to tackle rising unemployment and poverty. Qualitative method by presenting a systematic view of a phenomenon/symptoms, by detailing the relationship between variables. The results of the research produce government policies from various aspects as evidence of the government's efforts in accelerating handling and economic recovery, integrating and determining steps for implementing policies and the necessary breakthroughs as stated in Presidential Decree No. 82 of 2020. In conclusion, the role of the government is very much needed to help economic recovery Defense provided policies to the private sector during the pandemic in synergy with the community Together to help restore Indonesia's defense economy.